Estudio de Factibilidad para la creación de una sucursal de la empresa Roma Pizzería en el cantón Catamayo de la Provincia de Loja. - Pacheco Ludeña, Verónica Estefanía (2012)
Roma Pizzeria a company dedicated to the production of pizza has positioned itself in the local market leader both in its variety, quality and price of its products and its customer service and unique, this has enabled the trust and support of citizenship as well as the unconditional support of some sectors of the province. For this reason it was thought advisable to make this thesis topic Catamayo in Canton, which is called "Feasibility study for the establishment of a branch of the Roma Pizzeria in Canton Catamayo of the Province of Loja." The objectives for the development of this work are: Conduct a market study to determine whether it is feasible to implement a company branch Rome Pizzeria in Canton Catamayo, do a technical study to determine the project size, location and engineering thereof; perform a financial study using evaluation indices such as NPV, IRR, Sensitivity Analysis, Cost Benefit Value and Capital Recovery Period to meet its profitability and design the legal and administrative organization of the company. In the market study applied some methods and techniques among these we have the survey conducted on 370 families in the urban area of Guangzhou as well as Catamayo Pizzeria Manager Don Victorio to meet supply and demand for pizzas, making determining the demand existing unmet product under study. In engineering the project presents the production process in all its phases, in terms of size and location, is attached a map of the physical layout of the plant. It also indicates that the company will be located in the center of Canton Avenue Catamayo in Isidro Ayora and May 24. It will form a limited liability company with an investment of $ 23.003,04 the same partners who will contribute with 56,53% and 43,47% with a loan from the bank of Loja with an interest rate of 8.17% 5-year period and semiannual payments. The branch of the Pizzeria Roma in Catamayo dedicated to making and selling pizzas, lasagnas and tails will last 5 years. It has an organizational design functional, structural and positional as well as the elaboration of a manual of functions that allow a good development of activities and tasks of staff. With the economic-financial study established the price for each of the products and have for the first year $ 5,31 la Pizza, lasagna $ 6,95 and $0.43 the queue. According to the financial analysis: Net Present Value (NPV) of the project is $ 157.379,21 which ensures a return on the value of the company at the end of its useful life (5 years). Internal Rate of Return (IRR) of investment is 136,94% which is located well above the interest rate is 8.17%. The cost benefit ratio reaches $ 1.46 which means that for every dollar of investment is obtained 0.46 cents profit. Period of Investment Recovery Project is 11 months and 3 days. Likewise, the project supports an increase in the costs of 29,90% and a decrease in revenues of 22%. The research results demonstrate the feasibility of implementing the project, since it ensures profitability for investors and on the other hand allows a socio-economic development and business in the canton Catamayo, province of Loja, likewise is source of employment which will improve living standards.